2020
DOI: 10.1002/sctm.20-0284
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerves in the spotlight of the stem cell niche

Abstract: Niches are specialized tissue microenvironments that control stem cells functioning. The bone marrow mesenchymal stem cell niche defines a location within the marrow in which mesenchymal stem cells are retained and produce new cells throughout life. Deciphering the signaling mechanisms by which the niche regulates stem cell fate will facilitate the use of these cells for therapy. Recent studies, by using state‐of‐the‐art methodologies, including sophisticated in vivo inducible genetic techniques, such as linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 168 publications
(312 reference statements)
0
4
0
Order By: Relevance
“…During the past decade, surgical, pharma cological and genetic denervation models have established the nervous system's role in regulating the HSC niche 8 . But these studies mainly focused on sympathetic nerve fibres (those involved in involuntary actions of the body), showing that they help to maintain the functional integrity of the niche 9 . Here, Gao et al have found that the adhesion of HSCs to their bonemarrow niche and their ability to mobilize to the peripheral blood is controlled by nociceptive neurons acting directly on HSCs through secretion of the neurotransmitter CGRP.…”
mentioning
confidence: 99%
“…During the past decade, surgical, pharma cological and genetic denervation models have established the nervous system's role in regulating the HSC niche 8 . But these studies mainly focused on sympathetic nerve fibres (those involved in involuntary actions of the body), showing that they help to maintain the functional integrity of the niche 9 . Here, Gao et al have found that the adhesion of HSCs to their bonemarrow niche and their ability to mobilize to the peripheral blood is controlled by nociceptive neurons acting directly on HSCs through secretion of the neurotransmitter CGRP.…”
mentioning
confidence: 99%
“…For instance, it has been documented that the same drug that is used to denervate sensory neurons, resiniferatoxin (RTX), an analogue of capsaicin, also induces stress by causing hyperactivation of the sympathetic nervous system [ 16 , 62 , 157 ]. These studies also revealed that sensory nerves may tune down sympathetic nerve activity [ 16 , 62 , 105 ]. Sympathetic neurons release norepinephrine [ 70 , 123 ], which has been shown to strongly induce tumorigenesis [ 1 , 60 , 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in the excessive activation of sympathetic neurons, leading to the dysfunction of multiple organs (184,185). Finally, activation of PSNs can also attenuate sympathetic tone, as demonstrated in the bone marrow to regulate bone metabolism (186)(187)(188).…”
Section: Cancer Pain and Psychological Stressmentioning
confidence: 99%